The Changing Pattern of Certain Pediatric Infectious Diseases - M. Faried Kaspan (Indonesian Pediatric Society Publishing House, 2019)
In Indonesia results of efforts to attain a better quality of life in general, and the health development sector in particular are encouraging. Reduction of the number of cases admitted has been observed, and disease pattern seems to he changing. This article reviews the changing pattern of some infectious diseases in the Communicable Disease Ward, Department of Child Health dr Soetomo Hospital Surabaya. Further on it deals with the application of observations in respect of the Tridarma of the University e. i. Research, Education and Public/Medical seroice. Medical students, nowadays, have less practical experiences especially of the immunizable diseases. In the aspect of patient management, laboratory facilities seem to become more important, as the clinical manifestations of the diseases are less characteristic. Studies on the establisment of standard procedures for diseases that potentially become public health problems are needed.